Polar processing and development of the 2004 Antarctic ozone hole : first results from MLS on Aura - Santee, M. L.; Manney, G. L.; Livesey, N. J.; Froidevaux, L.; MacKenzie, I. A.; Pumphrey, H. C.; Read, W. G.; Schwartz, M. J.; Waters, J. W.; Harwood, R. S. (Geophysical Research Letters, 2006)
The Microwave Limb Sounder (MLS) on Aura is providing an extensive data set on stratospheric winter polar processing, including the first daily global observations of HCl, together with simultaneous measurements of ClO, HNO3, H2O, O3, N2O, and temperature (among others). We present first results charting the evolution of these quantities during the 2004 Antarctic late winter. MLS observations of chlorine deactivation and ozone loss during this period are shown to be consistent with results from the SLIMCAT chemical transport model NASA/JPL